Crossbreeding and consanguinity management in pig farms in the departments of Ouémé and Plateau in Benin - Dotché, Ignace; Idohou, Simon; DAHOUDA, Mahamadou; KIKI, Pascal; Govoeyi, Benoît; Antoine-Moussiaux, Nicolas; Dehoux, Jean-Paul; MENSAH, GUY APOLLINAIRE; FAROUGOU, SOUAÏBOU; Thilmant, Pierre; YOUSSAO ABDOU KARIM, ISSAKA; KOUTINHOUIN, G. BENOÎT (My University, 2019)
Aim: This study aims to characterize practices related to consanguinity management in pigs reared in Ouémé and Plateau. Materials and Methods: Crossbreeding and consanguinity data were collected from 60 farms in these two departments. Frequencies and averages were calculated and compared between departments, genetic types, and origin of progenitors. Results: The majority of the investigated pig farmers in both departments were married men of primary or secondary education level. Most of them cross animals without a specific crossbreeding scheme. These crossings were performed to a greater extent (p˂0.05) in Ouémé (94.28%) than in Plateau (52%). In general, farmers cross improved animals of high breeding values with the crossbred ones. These crossings were mainly performed to improve zootechnical performances. Renewing animals were commonly chosen from the farm or were provided from nearby farms. The majority of pig breeders in Ouémé (100%) and Plateau (86.67%) obtained reproductive animals from nearby farms. Males and females were sometimes bought from the same farm or from farms that pig breeders have sold reproductive animals in the previous years. In the case of selection within their own farm, male and female progenitors are separated at puberty by the majority of the breeders of Plateau (42.11%) and Ouéme (50%). Inbred mating was reported by breeders. More than half of breeders mate animals having a parental link in both departments. The mating was performed between animals of the same mother in 37.93% of farms in Ouémé and in 45.46% in Plateau. The main consanguinity consequences mentioned by the breeders were the high mortality at birth and weaning, piglets’ weakness at the birth, the slow growth, and the decrease in litter size. Sows with at least one parent from external farm had a litter size at birth and weaning and a live-born piglets’ number significantly higher than sows with both parents from the same farm. Conclusion: Rigorous monitoring of crossing and the filial links are necessary for pig farms for ensuring the improvement of zootechnical performances.
Keywords: consanguinity; crossbreeding; pig; zootechnical performances